Improvement of Retread Blends Composed of Natural Rubber(Nr) And Polybutadiene Rubber(Br) - alhatemy, mougd hadi; mahboba, mohammed hamed (Nahrain University College of Engineering Journal, 2008)
Tread of the tire is occasionally dislocated due o sever running on the road. Retreading is necessary in this case, and retread rubber compounds are made from a blend of NR/BR by using several additives like Activator Accelerator such as Zn salts of high molecular fatty acid (LAUREX) & homogenizing agents (Struktol- MS) produced by Uniroyal, Delayed Action Accelerators type Thiazoles and Sulfenamides such as (AMAX & MORFAX) produced by Vanderbilt.. insoluble sulfur, Pine Tar and others. An infinite number of rubber recipes are possible in blends. The best properties of each components are selected to achieve a blend having a wide spectrum of properties (recommended for retreading compounds) which is superior to that of the individual component and also economically competitive. The effect of using different levels(0.6,0.65,0.85pphr) of accelerators such as (AMAX & MORFAX) are enhancing the phsico-mechanical properties(tensile strength, modulus,shore hardness and abrasion resistance index), and the Activators Accelerator (LAUREX & Struktol- MS) in the rubber compounds are evaluated in such away that LAUREX is more affective in recipe no.3(2.5pphr) than the same level of Struktol-MS, so that it is making use of preparing suitable retreading rubber compound